Energy Harvesters and Self-powered Sensors for Smart Electronics - Shi, Qiongfeng; Liu, Huicong (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book is a printed edition of the Special Issue "Energy Harvesters and Self-Powered Sensors for Smart Electronics" that was published in Micromachines, which showcases the rapid development of various energy harvesting technologies and novel devices. In the current 5G and Internet of Things (IoT) era, energy demand for numerous and widely distributed IoT nodes has greatly driven the innovation of various energy harvesting technologies, providing key functionalities as energy harvesters (i.e., sustainable power supplies) and/or self-powered sensors for diverse IoT systems. Accordingly, this book includes one editorial and nine research articles to explore different aspects of energy harvesting technologies such as electromagnetic energy harvesters, piezoelectric energy harvesters, and hybrid energy harvesters. The mechanism design, structural optimization, performance improvement, and a wide range of energy harvesting and self-powered monitoring applications have been involved. This book can serve as a guidance for researchers and students who would like to know more about the device design, optimization, and applications of different energy harvesting technologies.